Vitamin D Deficiency in Obese Children and Its Relationship to Glucose Homeostasis - Olson, Micah L. (Endocrine Society, 2012)
OBJECTIVES: The aim of the study was to compare the prevalence of vitamin D deficiency in obese and non-overweight children in North Texas, to examine relationships between dietary habits and 25-hydroxyvitamin D [25(OH)D] level in obese children, and to examine the relationship between 25(OH)D level and markers of abnormal glucose metabolism and blood pressure. PATIENTS AND METHODS: Using a cross-sectional design, systolic and diastolic blood pressure, dietary information, serum 25(OH)D, fasting glucose and insulin, 2-h glucose from oral glucose tolerance test, hemoglobin A1c, and homeostasis model assessment of insulin resistance were recorded for 411 obese subjects (6–16 yr old) at an obesity referral clinic. 25(OH)D was also obtained from 87 control non-overweight subjects (6–16 yr old). RESULTS: Ninety-two percent of obese subjects had a 25(OH)D level below 75 nmol/liter, and 50% were below 50 nmol/liter. Among non-overweight subjects, these frequencies were 68 and 22%, respectively (both P < 0.01 compared with obese subjects). 25(OH)D was negatively associated with soda intake (P < 0.001), juice intake (P = 0.009), and skipping breakfast (P < 0.001). 25(OH)D was negatively correlated with homeostasis model assessment of insulin resistance (r = −0.19; P = 0.001) and 2-h glucose (r = −0.12; P = 0.04) after adjustment for body mass index and age but was not correlated with hemoglobin A1c, systolic blood pressure Z score, or diastolic blood pressure Z score. CONCLUSIONS: Vitamin D deficiency is common in children in this southern United States location and is significantly more prevalent in obese children. Lower 25(OH)D level is associated with risk factors for type 2 diabetes in obese children.